Transforming the therapeutic and nutritional benefits of Bougainvillea flowers for sustainable uses and food security - Pooja Mahey; Manmath Sontakke; Sangita Muchahary; Arun Kumar Gupta; Avinash Kumar Jha; Rohan Kandpal; Tanya Kunwar; Aditya Choudhary (Discover Food)
Abstract Bougainvillea, a widely recognized ornamental plant with ancient therapeutic uses, contains a rich array of bioactive compounds that exhibit pharmacological properties, including anti-diabetic, anti-inflammatory, antioxidant, anticancer, and antibacterial activities. This review systematically explores the traditional medicinal applications of Bougainvillea flower and bract extracts, particularly in managing conditions such as nausea, diarrhea, hypotension, gastrointestinal disorders, inflammatory diseases, and pain. The phytochemistry of bougainvillea is also highlighted, focusing on in vitro and in vivo evaluations of its bioactive components. Of the 18 species in the genus, Bougainvillea glabra, Bougainvillea × buttiana, and Bougainvillea spectabilis have been most extensively studied, revealing a diverse array of phytochemicals such as fatty acids, aliphatic hydrocarbons, volatile compounds, phenolics, flavonoids, and terpenes. These compounds have demonstrated promising pharmacological potential, positioning B. spectabilis and B. glabra as candidates for the development of novel therapeutic drugs, particularly as alternatives to conventional pharmaceuticals with fewer adverse effects. Furthermore, Bougainvillea shows significant promise in the food industry, where its flowers can be incorporated into functional foods and beverages, supporting food security and sustainable development. This review emphasizes the importance of further exploring the phytochemical diversity of Bougainvillea for its potential in both drug development and functional food innovation. Graphical Abstract